VOCABULARY IS AN IMPORTANT FACTOR IN TEACHING FOREIGN LANGUAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article is devoted to the issues of learning foreign languages, especially English as a second language. During the process of learning students should learn vocabulary units. In this article we try to identify the main points and give the best solutions.